2002
DOI: 10.1074/jbc.m205136200
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization, F-actin Interaction, and Membrane Association of the Ubiquitous Mammalian Coronin 3 Are Mediated by Its Carboxyl Terminus

Abstract: Coronin 3 is a ubiquitously expressed member of the coronin protein family in mammals. In fibroblasts and HEK 293 cells, it is localized both in the cytosol and in the submembranous cytoskeleton, especially at lamellipodia and membrane ruffles. The carboxyl terminus of all coronins contains a coiled coil suggested to mediate dimerization. We show here that in contrast to other coronin homologues, the recombinant human coronin 3 carboxyl terminus forms oligomers rather than dimers, and that this part is suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
138
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(157 citation statements)
references
References 36 publications
12
138
2
Order By: Relevance
“…In this study, we found that the C-terminal region of p57, p57 , had the similar actin-binding property as full-length p57, as demonstrated by co-sedimentation of expressed protein with F-actin in vitro and co-localization of expressed protein with actin cytoskeleton in vivo. These results revealed that the C-terminal region of p57 might also be responsible for binding F-actin which was consistent with actin-binding sites of other coronin-like proteins such as Xcoronin and Hcoronin3 [13,14].…”
Section: Results and Disscussion P57supporting
confidence: 56%
See 1 more Smart Citation
“…In this study, we found that the C-terminal region of p57, p57 , had the similar actin-binding property as full-length p57, as demonstrated by co-sedimentation of expressed protein with F-actin in vitro and co-localization of expressed protein with actin cytoskeleton in vivo. These results revealed that the C-terminal region of p57 might also be responsible for binding F-actin which was consistent with actin-binding sites of other coronin-like proteins such as Xcoronin and Hcoronin3 [13,14].…”
Section: Results and Disscussion P57supporting
confidence: 56%
“…However, it has been reported that the deletion of the C-terminal 65 amino acids from Xcoronin, a Xenopus homologue of coronin, significantly reduces its actin-binding activity [13]. In another report, the F-actin interaction of human coronin 3 (Hcoronin3) is mediated by its C-terminus [14]. These studies suggest that the C-terminus of p57 may contribute to its actin binding.…”
Section: Introductionmentioning
confidence: 94%
“…By contrast, FM4-64 uptake was inhibited in cells expressing GFP-fused dominant-negative coronin-3-ΔC, which bound GDP-Rab27a (Fig. 2C) without actinbundling activity (Spoerl et al, 2002) (Fig. 3C).…”
Section: Journal Of Cell Science 121 (18)mentioning
confidence: 96%
“…Therefore, residues 1-314 of coronin 3, which form the β-propeller structure for protein-protein interactions (Appleton et al, 2006), are essential for the binding to GDP-Rab27a. Rab27a-T23N preferentially interacted with coronin-3-N, coronin-3-WD, and coronin-3ΔC compared with coronin-3-WT, probably because Rab27a binding might be hindered by the C-terminus of coronin 3, which intramolecularly binds the N-terminus (Spoerl et al, 2002).…”
Section: Interaction Of Coronin 3 With Gdp-rab27amentioning
confidence: 99%
See 1 more Smart Citation